KEMAMPUAN MENULIS SURAT LAMARAN PEKERJAAN SISWA KELAS XII SMK NEGERI 1 MORAMO - Harmin (Jurnal Bastra (Bahasa dan Sastra), 2024)
Job application letters are very useful information in laying the foundation for understanding Indonesian and at the same time a strong foundation for the formation of students' scientific character. The research problem is "How is the ability of class XII students of SMK Negeri 1 Moramo in writing job application letters?" The purpose of this study is to describe the ability of class XII students of SMK Negeri 1 Moramo in writing job application letters. The instrument used in this study was writing a job application letter with three indicators as a reference, namely the systematic form of the letter, the suitability of the letter with EYD and the effectiveness of the letter sentences. The results of the study can be obtained information that from 35 respondents who were sampled in this study can be classified as follows, 29 respondents (94.28%) obtained the very capable category and 4 respondents (11.43%) obtained the capable category and 2 respondents (5.72%) obtained the less capable category. The highest category is the very capable category, so it can be concluded that the ability of class XII students of Moramo State Vocational School in writing job application letters in three aspects of ability is in the very capable category. It was concluded that on average the ability of class XII students of Moramo 1 State Vocational School in writing job application letters reached 82.31%. The average value is in the range of 65% - 84% with the capable criteria.